24th Annual Meeting of the German Society for Travel Medicine (DFR), Bremerhaven, Germany, 16–18 September 2021 - Küpper, Thomas (Health Promotion & Physical Activity, 2021)
About the Meeting This year the Annual Meeting off the German Society of Travel Medicine took place in Bremerhaven, September 16th to 18th. This traditional harbour town where thousands of Germans were embarking hundred years ago facing an uncertain future, the so-called “climate house” (an exihibtion about several aspects of the world’s climate) and the Alfred-Wegener Institute for Arctic Research were a fantastic setting for the meeting’s motto “traveling under extreme conditions”. After a brillant introduction by Stefan Kröpelin about research in the Sahara two weeks away from the next pharmacy and a fascinating lecture by Eberhard Kohlberg how to organize expeditions to Antarctica and how to work and to live there several lecturers illuminated a wide field of travel medicine in more or less extreme conditions.